Sistem Informasi Inventaris Berbasis Visual Basic.Net Pada Prodi Informatika ITB AAS Indonesia - Siti Rokhmah; Muhammad Ausathul Fikri; Putry Wahyu Setyaningsih (Universitas Mercu Buana Yogyakarta, 2023)
Inventory management is very important for managing and optimizing the sources and quantity of goods owned by the Informatics study program. To improve good inventory management in the Informatics study program of Institut Teknologi Bisnis AAS (ITB AAS), it is necessary to develop an inventory information system that can help manage study program inventory in a structured and transparent manner. In this research, it is proposed to develop an inventory information system based on Visual Basic.NET. This system develops applications that are used to manage inventory data within the ITB AAS Indonesia Informatics Study Program. This system is designed using the Visual Basic.NET programming language and has a user-friendly interface. In this system, users can carry out various activities such as searching for goods, borrowing, returning, and managing stock. In addition, this system is also equipped with user data management features and statistical reports to facilitate decision making. The application of Visual Basic.NET technology allows this system to have high speed and stability. In addition, an attractive and easy-to-understand interface design makes this system accessible to users from all walks of life, be it students, lecturers, or staff. With the Inventory Information System based on Visual Basic.NET in the Informatics Study Program ITB AAS Indonesia, it is hoped that inventory management will become more structured, transparent and efficient. This will improve the service quality of the ITB AAS Indonesia Informatics Study Program and provide great benefits for users.